Effect of low-frequency acupuncture on muscle and fascia stiffness: examination with or without intervention - Toshihiro Maemichi; Toshihiro Maemichi; Masatomo Matsumoto; Masatomo Matsumoto; Shigeru Meguriya; Atsuya Furusho; Takashi Yamashita; Toshiharu Tsutsui; Tsukasa Kumai (Frontiers in Rehabilitation Sciences)
BackgroundLow-frequency acupuncture is used to maintain skeletal muscle flexibility and improve joint range of motion; however, its definite effects are unclear. This study aimed to determine the effects of low-frequency acupuncture on muscle and fascial stiffness and ankle dorsiflexion range of motion.MethodsThe participants included 12 randomly selected healthy adults. The medial head of the gastrocnemius muscle was selected as the target muscle, and changes in hardness and dorsiflexion range of motion of the ankle joint in the deep fascia, muscle, and deep intermuscular fascia of the same region were measured before and after low-frequency acupuncture intervention. Acupuncture needles were inserted until they passed through the deep intermuscular fascia and electrically stimulated at a frequency of 2 Hz for 15 min. The 12 right legs were the intervention legs, and the 12 left legs were the non-intervention legs.ResultsIn the intervention leg, hardness increased in the deep fascia immediately after low-frequency acupuncture, but decreased in all regions (deep fascia, muscle, and deep intermuscular fascia) after 15 min. The rate of change in hardness was the greatest in the muscles and deep intermuscular fascia. Additionally, the ankle's dorsiflexion range of motion increased after 15 min. In contrast, the non-intervention leg showed no significant changes in stiffness or ankle dorsiflexion angle.ConclusionsLow-frequency acupuncture may decrease muscle stiffness and improve fascial gliding. The change in hardness tended to be greater in the deeper areas.